Effect of supplementing chromium histidinate and picolinate complexes along with biotin on insulin sensitivity and related metabolic indices in rats fed a high-fat diet - Orhan, Cemal; Küçük, Ömersman; Tuzcu, Mehmet; Şahin, Nurhan; Komorowski, James R.; Şahin, Kazım (Wiley, 2019)
Scope To investigate the effects of chromium histidinate (CrHis) and chromium picolinate (CrPic) complex along with biotin to a high-fat diet (HFD) fed to rats on the insulin sensitivity and the anti-obesity properties. Methods Forty-two Sprague-Dawley male rats were divided into six groups. The rats were fed either (a): a standard diet (Control) or (b): a HFD or (c): a HFD with biotin (HFD+B) or (d): a combination of HFD and biotin along with CrPic (HFD + B + CrPic) or (e): a combination of HFD and biotin along with CrHis (HFD + B + CrHis) or (f): a combination of HFD and biotin along with CrHis and CrPic (HFD + B + CrHis + CrPic). Results Adding biotin with chromium to HFD improved the glucose, insulin, HOMA-IR, leptin, lipid profile, with HFD+B+CrHis treatment being the most effective (p = 0.0001). Serum, liver, and brain tissue Cr concentrations increased upon Cr supplementations (p = 0.0001). Supplementing CrHis along with biotin to a HFD (HFD + B + CrHis) provided the greatest levels of GLUT-1, GLUT-3, PPAR-gamma, and IRS-1, but the lowest level of NF-kappa B in the brain and liver tissues. Conclusion Biotin supplementation with chromium complexes, CrHis in particular, to a HFD pose to be a potential therapeutic feature for the treatment of insulin resistance.
Keywords: biotin; chromium histidinate; chromium picolinate; GLUTs; high-fat diet